Profile Analysis of Hydrogenic Helium Ions in a Magnetized Sheet Plasma - Blantocas, Gene; Ramos, Henry (Science Diliman: A Journal of Pure and Applied Sciences; Vol 15 No 1 (2003), 2007)
The profile of hydrogenic helium ions in a magnetized sheet plasma was analyzed vis-à-vis the Collisional- Radiative (CR) model. Strong correspondence exists between experiment and theory, a significant portion of the characteristics of these singly-charged helium ions have been captured by the CR model. The features of the CR model can be aptly ascribed to a pure helium sheet plasma.